Pemanfaatan dan Ekonomi Lontar Bagi Masyarakat Di Kota Kupang - Marlistiyati Marlistiyati; Mahayasa Mahayasa; Marthen R. Pelokila (Bumi Lestari Journal of Environment, 2016)
This study was a descriptive study aimed to describe the form of the utilization of palm and its products as well as economic value is given, while also seeing how the other benefits of ejection for the surrounding environment, as well as how the shape of preservation for plants papyrus remain. This study was conducted in five village spread over 2 sub-district in the city of Kupang Namely District of Kelapa Lima (Ex. Oesapa and Kel. Lasiana), District Maulafa (Ex. Maulafa, Ex. Naimata, Ex. Penfui). The results showed that the population of ejection in the city of Kupang decreased dramatically due to the logging in the region much overgrown palm trees for the construction of both the tourist and residential., Selin was also in the utilization of palm majority of people take advantage of ejection based on knowledge own. Forms of utilization of ejection by the public more on making laru (alcoholic beverage) compared to utilization in other forms such as the manufacture of sugar and liquid sugar plate. It also forms other uses by the community that is in the manufacture of woven still own consumption and has not been introduced to the outside world, although there is the result of webbing that has been introduced to the international level (sasando) but even that would be done by a small group, while when seen in a tree palm has many benefits that can help improve the local economy. Research results also showed a lack of government attention to forms of utilization of these palm trees. Lontar will have value and economic benefit is higher when papyrus was given attention and assistance for people in their utilization thus increase the economic value to the community beneficiaries ejection. Based on these results submitted suggestions like society, the government and all parties concerned to keep attention ejection as one of the typical existing plants NTT. For the government dfan the relevant agencies need to continue to do the socialization and assistance to the community in terms of pemafaatan, processing and marketing of products or product ejection to be better known by the outside world and also needs to be an understanding for the community in the efforts to the preservation of plants palm that because other than plant papyrus that have direct benefits, papyrus also has services for the environment, so that the existence of ejection is maintained.